The role of transcription factors of neurosensory cells in non-syndromic sensorineural hearing loss with or without inner ear malformation. (3rd March 2016) - Zhou, Yuan; Qing, Jie; Dong, Yunpeng; Nie, Jin; Li, Jingkun; Wang, Chunmei; Liu, Yuyuan; Peng, Tao; Duan, Maoli; Liu, Xuezhong; Xie, Dinghua
Abstract: Conclusions : Previous studies have stated the roles and correlation of the four TFs (Sox2, Atoh1, Neurog1, and Neurod1) in the development of neurosensory cells. but whether they are inherited pathogenic factors to cause non-syndromic sensorineural hearing loss is unknown so far. This is the first time for screening the Sox2, Atoh1, Neurog1, and Neurod1 genes in children with NSHL. The c.133A > G in Neurod1 gene is a polymorphism, which is not associated with NSHL. Although these genes are the recognized TFs for modulating the development and transformation of NSCs, they may not be the inherited pathogenic factors to cause congenital severe or profound NSHL directly. Objective : To investigate the effect of the transcription factors (TFs) for the development of neurosensory cells (NSCs) and to explore the genetic etiology of congenital profound non-syndromic sensorineural hearing loss (NSHL). Methods : Children with NSHL, from multi-national and regional group, and control group were recruited to screen for the most common mutations for non-syndromic deafness among East Asian (mtDNA 12S rRNA: 1555A > G, 1494C > T; SLC26A4: IVS7-2 A > G, 2168 C > T). And mutational analysis of the coding regions in Sox2, Atoh1 and Neurog1, Neurod1 genes were performed. Results : Only the c.133A > G (p. Ala45Thr) in the Neurod1 gene was detected in this study. The allele frequencies of this variant were 88.00% and 84.88% in the inner ear malformation group and the normal inner ear group, respectively, while 90.85% of children in the control group carried c.133A > G. This variant existed in every group commonly and had no significant difference among them. No variant in the other two TFs was detected in this cohort.